1984
DOI: 10.1038/309182a0
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies distinguish between storage and secreted forms of eosinophil cationic protein

Abstract: The toxic effects of eosinophils on parasites and cells are due largely to the secretion of various granule proteins, following stimulation. In order to study this secretory process (degranulation) further, we have raised mouse monoclonal antibodies against both human eosinophil granule extracts and secretion products. From immunocytochemical studies it appears that one antibody, EG1 , recognized both the storage and secreted forms of eosinophilcationic protein (ECP), whereas antibody EG2 only bound to ECP dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
0
3

Year Published

1985
1985
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 298 publications
(113 citation statements)
references
References 23 publications
3
107
0
3
Order By: Relevance
“…3), EG1 reacted with ECP and EG2 reacted with ECP and EDN, consistent with the RIA findings. Overall, these results confirm the prior findings of Tai and colleagues [12] on the reactivity of EG1 and EG2 with ECP and EDN. Rosenberg and Tiffany reported that EG1 and polyclonal anti-ECP yielded three ECP bands on Western analyses, whereas EG2 detected only one ECP band at 18 kDa [34].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…3), EG1 reacted with ECP and EG2 reacted with ECP and EDN, consistent with the RIA findings. Overall, these results confirm the prior findings of Tai and colleagues [12] on the reactivity of EG1 and EG2 with ECP and EDN. Rosenberg and Tiffany reported that EG1 and polyclonal anti-ECP yielded three ECP bands on Western analyses, whereas EG2 detected only one ECP band at 18 kDa [34].…”
Section: Discussionsupporting
confidence: 83%
“…The monoclonal antibodies EG1 and EG2 were developed to further understand this degranulation, or secretory, process and to identify activated eosinophils in tissues. EG1 was thought to react with both stored and secreted forms of ECP, whereas EG2 was thought to react with EDN and only secreted ECP [12]. In addition, unactivated normal blood eosinophils reacted only with EG1, but activated eosinophils reacted with both EG1 and EG2, suggesting that EG2 selectively identified secreting activated eosinophils [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations